The Role of Philosophy of Science in the Development of Scientific Methods for Islamic Studies - Rifqi Fathan Saepudin Muzakki; Nabila, Nabila Hasna Rafilah; Muhamad Parhan; Muhamad Mauris Faruqi Ali; Gina Fauzia Adnin (STAI Terpadu Yogyakarta, 2025)
The scientific method has become an important foundation in the development of science, its application in Islamic studies still faces challenges in terms of integration with Islamic values, especially in the midst of the development of the Industrial Revolution 4.0. In-depth studies that combine modern technology with the perspective of Islamic philosophy of science are still limited, so more comprehensive research is needed to fill this void. This research explores the role of philosophy of science in the development of scientific methods in the context of Islamic studies. In the era of the Industrial Revolution 4.0, the scientific method plays an important role in various aspects of life, including in the application of information and communication technology that requires a strong scientific basis. This article highlights the close relationship between philosophy of science and Islam, especially in providing an epistemological basis that allows the integration of scientific methods with Islamic values. A literature study approach is used to examine various sources regarding the development of the scientific method as well as the application of philosophy in Islamic studies. The results show that philosophy of science not only provides a theoretical foundation for the scientific method, but also directs its application to be in accordance with spiritual and moral values in Islam